2006
DOI: 10.1103/physrevb.74.125421
|View full text |Cite
|
Sign up to set email alerts
|

Small-radius clean and metal-doped boron carbide nanotubes: A density functional study

Abstract: We present the results of ab initio density functional theory calculations of the atomic and electronic structure of small radius boron carbide nanotubes, and the effects of doping these tubes with Li and Cu atoms. We have found that undoped narrow tubes are more energetically favorable than the corresponding boron carbide strips. The effects of doping on the atomic and electronic structure of these tubes have been found to be dependent on the size and symmetry of the tubes, and the type of dopant atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…B. Nanotube materials A carbon nanotube can be thought of as a sheet of graphite rolled up into a seamless hollow cylinder. Similarly, boron nitride, boron carbide and silicon can all form graphite-like nanotubes [11,12,[24][25][26][27][28][29][30][31]. However, silicon nanowires have been observed much more readily [32] due to the preference of sp 3 bonding [33], despite this, silicon nanotubes have been reported experimentally [30,31].…”
Section: A Interaction Energy Acceptance and Suctionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Nanotube materials A carbon nanotube can be thought of as a sheet of graphite rolled up into a seamless hollow cylinder. Similarly, boron nitride, boron carbide and silicon can all form graphite-like nanotubes [11,12,[24][25][26][27][28][29][30][31]. However, silicon nanowires have been observed much more readily [32] due to the preference of sp 3 bonding [33], despite this, silicon nanotubes have been reported experimentally [30,31].…”
Section: A Interaction Energy Acceptance and Suctionmentioning
confidence: 99%
“…Single-walled nanotubes may be formed from a range of materials, such as carbon, boron nitride, boron carbide and silicon [10], and the list of possible materials is constantly growing [11]. Since their discovery, carbon nanotubes have generated considerable research and development for nanomechanical devices due to their demonstrated remarkable and unique electrical, mechanical, and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotubes formed from various layered materials of the AlB 2 type that have so far been studied include structures based on MgB 2 , 10,11 AlB 2 , 9-11 silicon diboride, 11 BeB 2 , 12 ScB 2 , 10 TiB 2 , 10,13 Ca/ Sr͑Al 0.5 Si 0.5 ͒ 2 , 14 and LiBC. 10,15,16 LiBC is isoelectronic to MgB 2 and it has been shown theoretically that hole doping of layered LiBC leads to an increase in electronphonon coupling which might result in an increase in T C . 17 Calculations by Mehl et al 18 have also shown that the full replacement of the Mg atoms in MgB 2 by Cu, and the partial replacement of boron atoms by carbon, to form a CuBC-like layered compound, might increase its transition temperature to ϳ50 K.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, 16 we have reported results of ab initio plane-wave pseudopotential density functional theory ͑DFT͒ calculations of infinite, isolated, small-diameter clean, and Li-and Cu-doped, boron-carbide ͑BC͒ nanotubes. Very narrow nanotubes are predicted to possess intriguing physical properties ͑such as possible enhancement of the electronphonon coupling͒ due to the effects of electron confinement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation